Postoperative radiotherapy improves disease-free survival of EGFR wild-type pN2 non-squamous-cell non-small-cell lung cancer (Nsq-NSCLC) patients after complete resection: a propensity score matching analysis - Yunsong Liu; Yu Men; Xu Yang; Shuang Sun; Yongxing Bao; Zeliang Ma; Yang Wang; Yirui Zhai; Jianyang Wang; Lei Deng; Wenqing Wang; Nan Bi; et al. (Radiation Oncology)
Abstract Background The ADAURA study indicated that adjuvant TKI therapy improves survival in postoperative patients with EGFR-mutated (EGFRm) non-small-cell lung cancer (NSCLC), especially in stage III disease. However, the effect of PORT for stage III (N2) NSCLC with different EGFR statuses remains unclear, which we aimed to investigate in the present study. Methods Between 2006 and 2019, consecutive patients with pN2 non-squamous cell NSCLC (Nsq-NSCLC) after complete resection and adjuvant chemotherapy or EGFR tyrosine kinase inhibitor (TKI) who had detection of EGFR status were retrospectively analyzed. PORT was administered using IMRT at 2 Gy per fraction with a total dose of 50 Gy over 5 weeks. Patients were categorized into 4 groups according to EGFR status and treatment: EGFR wild-type (EGFRwt) PORT group, EGFRwt non-PORT group, EGFRm PORT group, and EGFRm non-PORT group. Propensity score matching (PSM) was used to compensate for differences in baseline characteristics. The Kaplan-Meier method and log-rank test were used to evaluate disease-free survival (DFS), locoregional relapse-free survival (LRFS), and distant metastasis-free survival (DMFS). Results A total of 566 patients were enrolled: 90 in the EGFRwt PORT group, 154 in the EGFRwt non-PORT group, 111 in the EGFRm PORT group, and 211 in the EGFRm non-PORT group. After PSM, the median DFS in the EGFRwt PORT group versus the EGFRwt non-PORT group were 33.9 versus 17.2 months (HR 0.62, 95%CI 0.417–0.920, P = 0.017). In EGFRwt groups, PORT also improved LRFS (HR 0.58, 95%CI 0.34–0.99, P = 0.042) and DMFS (HR 0.649, 95%CI 0.43–0.98, P = 0.038). In EGFRm groups, PORT only improved LRFS (HR 0.50, 95%CI 0.30–0.85, P = 0.009), with no significant difference in DFS or DMFS between the PORT and non-PORT groups. Conclusion For patients with completely resected pN2 Nsq-NSCLC receiving adjuvant chemotherapy, PORT may improve DFS in EGFRwt patients but not in EGFRm patients. Randomized clinical trials are needed for validation.